ORGAN-PRESERVING INTERVENTIONS IN SURGICAL CORRECTION OF SPLEEN CYSTS IN CHILDREN - Andriy Kuzyk (Acta Medica Leopoliensia, 2023)
The surgical approach to splenic cyst treatment in children is rather controversial. There are different organ-preserving surgeries available to treat children with the spleen affected by cystic lesions. These surgical interventions are thoroughly discussed in various sources.